PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA - Dyah Setyawati, 15.05.52.0284; Puspitasari, Elen (Students' Journal of Accounting and Banking, 2019)
This research aims to examine and analyze the influence of Profitability, Leverage, Company's Size, Company’s Age, Board of Commissioners, Audit Committee, Institutional Ownership, Public Ownership, and Environmental Performance to Corporate Social Responsibility (CSR) Disclosure on the mining companies were listed on the Indonesia Stock Exchange for period 2012-2017. Population used are mining companies that listed on Indonesia Stock Exchange for period 2012-2017. The samples selection are using a purposive sampling method. The analysis tool used in this research is multiple linear regression analysis. The results of the research show that Company’s Size and Company's Age has positive and significant on CSR disclosure. Environmental Performance has negative and significant on CSR disclosure. Profitability, Audit Committee, and Public Ownership has positive, but not significant on CSR disclosure. Leverage, Board of Commissioners, and Institutional Ownership has negative, but not significant on CSR disclosure.